Testicular gangrene complicating strangulated groin hernia in an adult - Gbenga, Olaogun Julius; Temi, Adegun Patrick; Adetunji, Omotayo John; Olufemi, Areo Peter; Ayokunle, Dada Samuel (International Surgery Journal, 2017)
Testicular infarction/gangrene is most commonly secondary to testicular torsion. Testicular infarction complicating a strangulated inguinal hernia has been well documented in pediatric literature but found to be rare in adults as it has only been reported in only 2 cases and none of which required orchidectomy for treatment. We report a rare case of strangulated inguinoscrotal hernia with testicular gangrene following a delayed presentation in a 25 year old boy with neglected groin hernia. The patient had orchidectomy in addition to primary bowel resection and anastomosis.